Modelling intercontinental tourism consumption in South Africa: a systems-of-equations approach - (:unkn) unknown (My University, 2013)
This article investigates the pattern of inbound tourists’ consumption in South Africa, examining four main intercontinental markets and five different tourism goods. The empirical investigation develops an AIDS model and it extends recent research by allowing tourists to base their spending decision on the real effective price differences between South Africa and their home country. The results show that tourist spending in South Africa is a luxury good and tourists react normally to a change in the relative price of goods. The cross-price elasticities suggest that the preferences of different markets influence their view of substitutability and complementary effects between various products in South Africa.
Keywords: African Research